INFORMATIKA HÁM IT PÁNINDE JOYBAR METODÍNAN PAYDALANÍWDÍŃ ZÁRÚRLIGI - Ilyasova, Z.K. (ILIM hám JÁMIYET, 2024)
The article discusses the stages, methods, results of using the project method in teaching computer science and IT in secondary schools, as well as the need.